Development of Bowling Career Media to Improve Students’ Understanding toward Career Exploration - Annisa Sofiana; Agus Basuki (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to develop bowling career media to improve students' understanding of career exploration. The development was based on using the Borg and Gall development model adopted up to the 6th stage. Ten students from grade X of SMA Negeri 1 Bantul selected the subject using a purposive sampling technique. The instrument covered expert validation sheets, career exploration tests, and questionnaires for students. The data were analyzed quantitatively and qualitatively. Based on the expert validation result, the feasibility of the product reached a score of 89.4 with great glory. The product trial results showed that the student response value of 90.6 with an outstanding category and the product's effectiveness showed an average increase between the pre-test and post-test scores. The experimental activities had a significant positive effect. Overall, bowling career media are considered feasible and effective to improve students' understanding of career exploration.